Design of catalysts comprising a nickel core and ceria shell for hydrogen production from plastic waste gasification: an integrated test for anti-coking and catalytic performance. Issue 12 (28th May 2020) - Wu, Shan-Luo; Kuo, Jia-Hong; Wey, Ming-Yen
Abstract : A novel core–shell catalyst with high coking resistance ability was applied for hydrogen production from plastic waste. Abstract : In this study, a core–shell structured catalyst composed of a nickel core coated with a high thermal-stability shell layer was prepared for the decomposition of waste plastics to produce hydrogen. Ceria–zirconia mixed metal oxide was used as the coating layer to protect the active phase of the catalyst. The as-prepared catalyst was firstly tested using a methane cracking process to evaluate its stability under high temperature and coking conditions. The special redox characteristics of the Ni@CeO2 –ZrO2 core–shell-structured catalyst provide lattice oxygen to oxidize carbon produced during the reaction and extend the life of the catalyst during the coking resistance test. Different pore sizes in the functional shell were prepared by adding a templating agent, and the catalyst was tested for its ability to produce hydrogen from plastic waste. The CeO2 –ZrO2 shell promoted the production of active oxygen species and enhanced the dispersion of the Ni cores, which are beneficial attributes for plastic waste decomposition.